Correction: PAMAM/5-fluorouracil drug conjugate for targeting E6 and E7 oncoproteins in cervical cancer: a combined experimental/in silico approach. Issue 19 (13th February 2017) - Rengaraj, Arunkumar; Subbiah, Balaji; Haldorai, Yuvaraj; Yesudhas, Dhanusha; Yun, Hyung Joong; Kwon, Soonjo; Choi, Sangdun; Han, Young-Kyu; Kim, Eung-Soo; Shenpagam N., Hema; Huh, Yun Suk
Abstract : Correction for 'PAMAM/5-fluorouracil drug conjugate for targeting E6 and E7 oncoproteins in cervical cancer: a combined experimental/ in silico approach' by Arunkumar Rengaraj et al., RSC Adv., 2017, 7, 5046–5054.